Peningkatan Kompetensi Guru dalam Pemanfaatan Teknologi Kecerdasan Buatan sebagai Penunjang Media Pembelajaran di Sekolah Alam - Saputra, Imam; Wardayani, Wardayani; Sari, Dian Purnama; Supriyanto, Supriyanto; Hidayat, Rahmat (Forum Kerjasama Pendidikan Tinggi, 2026)
The rapid development of Artificial Intelligence (AI) technology requires educators to possess adaptive digital literacy to enhance the quality of learning. This international community service project aims to improve the competence of teachers at Sekolah Alam Istana Hati Binjai in utilizing AI technology as a supporting instrument for learning media. The initiative was spearheaded by the ADA Research Center through strategic collaboration with Universiti Utara Malaysia (UUM), the Indonesian Institute of Technology and Business, and various other supporting higher education institutions. The method employed was Collaborative Community Engagement, featuring intensive workshops and personalized hands-on mentoring for 16 teachers across elementary, junior high, and senior high school levels. The training focused on understanding AI ethics, prompt engineering, and the creation of automated visual learning media. The results demonstrated a significant increase in the participants' digital literacy, with the average evaluation score rising from 48.5 to 86.0. All participants (100%) successfully produced digital learning media relevant to the nature school curriculum. The discussion in this article highlights that cross-country collaboration provides global motivation for local educators to adopt technology without abandoning environment-based educational philosophies. It is concluded that strengthening AI literacy for teachers is a crucial step in minimizing the digital divide and improving the efficiency of educational administration at the nature school level